Nega in vzgoja visokovrednega lesa - Polajnar, Tomaž (Gozdarski vestnik, 2008)
The article shows the significance of forest treatment with the emphasis on the growing of individual trees as a possibility for increasing the yield value and decreasing the investment costs for the forest owners. It presents the possibilities for growing high quality wood of deciduous trees and emphasizes the necessity of the correct wood evaluation by the means of pruning.
Keywords: forestry; gozdarstvo; pogozdovanje; nega gozdov